ANALISIS LINGKUNGAN BISNIS INDUSTRI JAMU TRADISIONAL (Studi pada PT. Sido Muncul Semarang) - Suhaji, Suhaji (PRESTASI, 2011)
Traditional medicine industries (Jamu Tradisional) in Indonesia face many challenges. The bad image from herb industries that use chemical (BKO), foreign competitors, and few government contribution, makes the traditional medicine business environment becomes more complex. This study aims to analyze the business environment of traditional medicine industries, especially of PT Sido Muncul from the external environment, industries competitive from Porterâs model and SWOT Analysis. The result of analysis shows that from three business environment, PT Sido Muncul has many strengths to compete in Traditional medecine industries. Although there are many challenges, but there are still many opportunities in that industry. PT Sido Muncul, one of the herb industry leaders in Indonesia, had to be good response to the environment and by its strength, the company will have good prospect in the future.Keywords: Business Environment, Traditional Medicine